Sperm fertility and viability following 48 h of refrigeration: Evaluation of different extenders for the preservation of bull semen in liquid state - Crespilho, A. M.; Nichi, M.; Guasti, P. N. [UNESP]; Freitas-Dell'Aqua, C. P. [UNESP]; Sa Filho, M. F.; Maziero, R. R. [UNESP]; Dell'aqua Junior, José Antônio [UNESP]; Papa, Frederico Ozanam [UNESP] (Elsevier B.V., 2014)
Two experiments were conducted to compare the effectiveness of different extenders conventionally used for semen cryopreservation to maintain the viability and fertility of cooled bull semen. In Experiment 1, sperm samples obtained from 20 Nellore bulls were preserved at 5 C for 48 h using two extenders containing 20% of egg yolk [Tris (TRIS-R) and Botu-Bov (R) (BB)] and another composed of 1% soy lecithin [Botu-Bov -Lecithin (BB-L)] as substitutes for animal origin products. The samples were evaluated at 6, 24 and 48 h for plasma and acrosomal membrane integrity, quantification of thiobarbituric acid reactive substances (ng of TBARS/10(8) cells) and sperm motility parameters by computer-assisted semen analysis (CASA). In Experiment 2, pregnancy rate (P/AI) of 973 fixed-time artificially inseminated Nellore cows were compared when cows were inseminated with conventionally cryopreserved semen in TRIS-egg yolk glycerol (TRIS-C Control, n =253) or semen cooled for 48 h in TRIS-R (n = 233), BB (n =247) or BB-L (n =240). Although none of the extenders used was effective on maintaining total progressive motility and cellular integrity throughout the 48h of the refrigeration period (P <0.01), BB-L conferred greater protection against oxidative stress (P< 0.05) than egg yolk-based medias. The P/AI for semen samples preserved in TRISC, TRIS-R, BB and BB-L were 39.92(a), 25.32(b), 26.32(b) and 33.33(ab), respectively. These results demonstrate that the three conventional extenders used for semen cryopreservation do not provide the protection required to maintain bull semen fertility under refrigeration for a 48h period, resulting in reduced pregnancy rates. However, the use of lecithin-based medium instead of egg yolk results in greater protection against lipid peroxidation, producing P/AI results comparable to those obtained using frozen semen. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Bull; Semen extender; Soy lecithin; Sperm refrigeration; Lipid peroxidation